Simulations on organic Rankine cycle with quasi two-stage expander under cross-seasonal ambient conditions - Wang, Hai-Xiao; Lei, Biao; Wu, Yu-Ting (Applied thermal engineering, 2023)
•A model of ORC in variable condensing ambient conditions was developed.•Using quasi two-stage expander to improve the cross-seasonal performance of ORC.•The cooling power consumption was computed in different operating conditions. Organic Rankine cycle (ORC) plays an important role in addressing the issue of energy shortage and climate change. The condenser should release heat to the environment. Due to the seasonal and daily variations of ambient conditions, the condensation temperature, power consumption of the cooling system, the operation conditions of the working medium pump and expander would suffer drastic changes in different condensing ambient conditions. Therefore, the main aim of this study is to investigate the cross-seasonal performance of the organic Rankine cycle under variable condensation conditions. Simultaneously, the single screw expander with quasi two-stage expansion was used to improve the performance of ORC in different condensing ambient conditions. A model was developed to depict the variations of operation parameters of ORC system. The results show that the performance of ORC was adversely correlated with the wet-bulb temperature throughout the year. The net power and net efficiency can be reached at 8.04 kW and 11.31 % when the wet-bulb temperature is 1.1 ℃, respectively. Additionally, the variation in cooling water flow rate has little effect on the volumetric expansion process of the new single screw expander, but has a significant influence on the velocity expansion process, which increases by nearly 56.4 %. Meanwhile, decreasing the pipeline impedance coefficients of cooling system can optimize ORC system performance effectively. It was also discovered that the isentropic efficiency of single screw expander decreases by only 8.68 percentage points during the expansion ratio increase from 3.31 to 11.54.